Implementasi Metode Fuzzy K-Nearest Neighbor Untuk Identifikasi Cedera Pada Pemain Futsal - Rizki Wulyono Propana Sodiq; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The injury is common place occurs in a sports game. The risk of injury is a State when the individual risk hazards due to perceptual deficit gets or physiological, lack of awareness about the dangers, or old age. Injuries that are often experienced by invistasi futsal futsal players between HIGH SCHOOL/Central Java-se Equal the year 2013, namely the head injuries that often occur in the eyes of 31.8%, upper limb injuries often occur at the wrist, 33 3%, a lower limb injury often occurs in the knee injury to 36% and togok an injury often occurs at the waist 65.38%. Being the overall percentage of injuries that happen on most body limbs down 47.18%, especially on the knees of 36%. Fuzzy K-NN classification is a method that combines technique with fuzzy K-Nearest Neighbor Classifier. Algorithms of Fuzzy K-Nearest Neighbor gives value to the membership class on test data rather than putting test data on a particular class. FK-NN classification is a method used to predict the test data using the value of the degrees of membership test data on each class. The required variable in this study was injury symptoms. Highest accuracy of the test results is when K = 5 the value of 94,29%.